2018
DOI: 10.3390/nu10040514
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Neuroprotection of Total Glucosides of Paeoniae Radix Alba against Semen Strychni-Induced Neurotoxicity in Rats: Suppressing Oxidative Stress and Reducing the Absorption of Toxic Components

Abstract: Strychnos alkaloids (SAs) are the main toxic constituents in Semen Strychni, a traditional Chinese medicine, which is known for its fatal neurotoxicity. Hence, the present study was carried out to evaluate the neurotoxicity induced by SAs and the pre-protective effects of the total glucosides of Paeoniae Radix Alba (TGP). An SA brain damage model was firstly established. The neurotoxicity induced by SAs and the pre-protective effects of TGP were confirmed by physical and behavioral testing, biochemical assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Besides, several studies have shown that RB, RPA, and their main active ingredients (such as saikosaponins, albiflorin, methyl gallate, etc.) have significant neuroprotective and antidepressant activity ( Wang et al, 2016 ; Li et al, 2017 ; Li et al, 2018 ). Therefore, we speculated that the combination of RB and RPA by increasing the bioavailability of these five phytochemicals, the impact on picolinic acid was strengthened to enhance each other’s neuroprotective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, several studies have shown that RB, RPA, and their main active ingredients (such as saikosaponins, albiflorin, methyl gallate, etc.) have significant neuroprotective and antidepressant activity ( Wang et al, 2016 ; Li et al, 2017 ; Li et al, 2018 ). Therefore, we speculated that the combination of RB and RPA by increasing the bioavailability of these five phytochemicals, the impact on picolinic acid was strengthened to enhance each other’s neuroprotective.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, several studies have shown that RB, RPA, and their main active ingredients (such as saikosaponins, albiflorin, methyl gallate, etc.) have significant neuroprotective and antidepressant activity (Wang et al, 2016;Li et al, 2017;Li et al, 2018). Therefore, we speculated that the FIGURE 9 | The correlation between the phytochemicals improved bioavailability after compatibility and the altered endogenous metabolites.…”
Section: Picolinic Acidmentioning
confidence: 99%
“…Evidence have shown that Semen Strychni could enhance oxidative stress. 4 Uric acid is the nal oxidation product of purine metabolism and can provide an antioxidant defense. 30 Similar to uric acid, ascorbic acid-2-sulfate could also protect the body from oxidative stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…When used in large dosage or for a long time, it can easily cause multiple organ damage, such as liver injury, kidney injury as well as nerve injury. 4,5 Thus, it is of great signicance to clarify the toxic mechanism and seek a suitable antidote.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effects of RPA on the nervous system can be summarized as follows: neuroprotective, antidepressant, sedative, and analgesic and anticonvulsant. Total glucosides of paeony can exhibit pre-protection against neurotoxicity by reducing the absorption of toxic alkaloids by the brain (Hou et al, 2017;Li et al, 2018). Albiflorin is the main ingredient of RPA, and it can lower the levels of neuronal nitric oxide synthase (nNOS), and the antinociceptive activity is at least partially related to calcium channels (Zhang et al, 2016b).…”
Section: The Pharmacological Actions Of Rpamentioning
confidence: 99%